Driving anger and its relationship with aggressive driving among Chinese drivers. (July 2018) - Zhang, Tingru; Chan, Alan H.S.; Li, Shuling; Zhang, Wei; Qu, Xingda
Highlights: The 14-item DAS was adapted for use with Chinese drivers. A three-factor DAS structure provided a good fit to the data obtained. The relationships with aggressive driving were different across anger types. Chinese drivers had lower levels of driving anger than drivers in Western countries. Anger-aggression association was stronger in China than that in Western countries. Abstract: Driving anger poses a serious threat to road safety. Increasing attention is being paid on this issue, with driving anger usually measured by a 14-item version of the Driving Anger Scale (short DAS). However, driving anger problem in China has received limited research attention and there is no corresponding Chinese version of the short DAS. This study adapted the short DAS for use with Chinese drivers and investigated the relationship between driving anger and aggressive driving with an Internet-based survey conducted to a sample of Chinese drivers. The Confirmatory Factor Analysis results showed that a three-factor DAS structure provided a good fit to the data obtained, with the three subscales used being hostile gesture, safety-blocking and arrival-blocking. The hostile gesture subscale and arrival-blocking subscale were positive predictors while the safety-blocking subscale was a negative predictor of aggressive driving. In China, the overall driving anger was lower but its association with aggressive driving was stronger, than that in western countries. These findings provide important insights into causes and consequences of driving anger for the development of effective strategies to reduce driving anger and to enhance road safety.